Conjunctival and pulmonary hemodynamic properties in sickle cell disease subjects with and without pulmonary hypertension. Issue 12 (6th November 2015) - Kord Valeshabad, Ali; Wanek, Justin; Molokie, Robert E.; Machado, Roberto F.; Gordeuk, Victor R.; Shahidi, Mahnaz
Key Clinical Message: Conjunctival microvascular hemodynamic alterations were reported for the first time in sickle cell subjects with and without pulmonary hypertension. Assessment of the conjunctival microcirculation using noninvasive imaging may improve understanding of microvascular hemodynamic alterations that occur due to pulmonary hypertension in sickle cell disease. Abstract : Conjunctival microvascular hemodynamic alterations were reported for the first time in sickle cell subjects with and without pulmonary hypertension. Assessment of the conjunctival microcirculation using noninvasive imaging may improve understanding of microvascular hemodynamic alterations that occur due to pulmonary hypertension in sickle cell disease.